Evaluation of optimal sampling interval for activity monitoring in companion dogs - Dow, Caitlin (2009)
OBJECTIVE: To determine by use of an accelerometer the sampling interval that has the least variable total activity counts from one week to the next in companion (ie, nonlaboratory) dogs. ANIMALS: 80 dogs. PROCEDURES: Dogs wore an accelerometer continuously for 2 weeks. Between-dog and within-dog day-to-day variability in total activity counts were evaluated. The changes in counts between week 1 and week 2 were compared for weekdays, weekends, and full weeks. RESULTS: Significant between-dog variability in total activity counts was detected. Within dogs, there was significant day-to-day variability, with highest counts recorded on weekends. In comparison of data from the first week with data from the second week, the greatest differences were in weekend counts (median difference, 21%; range, 0% to 154%) and the smallest differences were in full 7-day counts (median difference, 10%; range, 0% to 74%). Comparison of weekday counts revealed a median change of 12% (range, 0% to 104%). CONCLUSIONS AND CLINICAL RELEVANCE: Significant between-dog variability in total daily activity counts was detected. Within dogs, a full 7-day comparison of total activity counts from one week to the next provided the least variable estimate of the dogs’ activity. For dogs in their home environment, the activity monitor may be most useful in following changes in activity over time. For dogs that have no change in routine according to the owner’s report, the least variable estimates of activity can be collected by comparing activity in 7-day intervals.